Novel ssDNA Ligand Against Ovarian Cancer Biomarker CA125 With Promising Diagnostic Potential - Tripathi, Pranav; Sachan, Manisha; Nara, Seema (Frontiers in Chemistry, 2020)
In-vitro diagnostic industry is always striving to explore specific and high-affinity recognition entities, sensitive probes and newer technology or platforms to develop disease detection methods with lesser production cost, time and minimum interference or variability. Aptamers suffices as reliable recognition element by addressing issues as mentioned earlier. Hence, this work focuses on screening high-affinity ssDNA ligands to capture an exemplary biomarker CA125 using membrane-SELEX technology coupled with aptainformatics (translational bioinformatics using aptamers). The ssDNA ligands or aptamers have been screened and characterized extensively, through an array of assays to ensure a valuable diagnostic potential with KD (dissociation constant) of 166 nM. The robustness of the selected aptamer ligand 2.26 and its complex with target CA125 is investigated in the presence of serum and extreme salt concentrations. Its diagnostic potential is convincingly demonstrated by running a competitive Nucleic acid Lateral Flow Assay at various sample concentrations. The ssDNA ligand reported in this manuscript holds immense potential in the detection and specific targeting of CA125 biomarker.